Two new species of Crepidotus (Basidiomycota, Agaricales) from peninsular India - Kumar, A. Manoj; Vrinda, K.b.; Pradeep, C.k. (Phytotaxa, 2018)
Two new species, Crepidotus volubilis and Crepidotus palodensis are described from Kerala State, India based on morphological and molecular (nrLSU) phylogenetic data. The new taxa were assigned to section Echinospori due to the verrucose basidiospores and presence of clamp connections in the hyphae. Comprehensive descriptions, photographs and comparisons with phenetically similar and phylogenetically related species are discussed. The nrLSU-based phylogenetic analysis performed using Maximum Likelihood (ML) method, supported the novelty of the species.